Health status and health care utilization profiles of adolescents with disabilities - Shauna Kingsnorth; Yani Hamdani; Clare Cheng; Sally Lindsay; Joanne Maxwell; Angela Colantonio; Mark Bayley; Colin Macarthur (Health Care Transitions, 2023)
Background: Adolescents with physical disabilities of childhood often require a transition from pediatric to adult systems as part of life-long, comprehensive health care once they reach 18 years of age. The process of transition can be complex, challenging, and influenced by health-related factors and availability of health care resources. Objective: To provide a baseline profile of health-related quality of life, health management, social participation, and health care utilization for adolescents 16 years of age with spina bifida (SB), acquired brain injury (ABI), or cerebral palsy (CP) in Toronto, Canada. Methods: A cross-sectional survey design was used. A sample was drawn from a large, urban pediatric rehabilitation hospital as part of a prospective, longitudinal, observational mixed-methods study. Seven English language, paper-copy standardized measures were completed; measures were organized across the three domains of interest. Health care utilization data were obtained from population-based, health services administrative datasets held by ICES. These data included outpatient physician visits, emergency department visits, and hospitalizations over a 12-month period, beginning at their 16th birthday. Results: The sample comprised 99 participants: survey measures were completed by 59 participants (12 SB, 19 ABI, and 28 CP) and health care utilization obtained for 92 participants (19 SB, 25 ABI, and 48 CP). Baseline scores across measures and rates of health care utilization are provided. All three groups reported relatively good health-related quality of life. Youth with CP had lower scores on health utility, health management, and social participation, compared with the SB and ABI groups. Youth with SB had slightly higher health care utilization in the 12-month period after their 16th birthday, compared with the ABI and CP groups. Conclusions: This cross-sectional survey collected comprehensive health status and health care utilization data on 16-year-old youth with SB, ABI, and CP in Toronto, Canada. With few exceptions, the CP group consistently scored lower across measurement domains. These baseline data may be useful for hospital administrators, policy makers, and researchers examining changes in health-related quality of life, health management, social participation, and health care utilization among youth with SB, ABI, and CP, particularly in the context of transition planning and evaluation.